Impacto da adesão ao protocolo de sepse na sobrevida de pacientes com infecções comunitárias e relacionadas a assistência a saúde - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Sepsis is defined as a dysregulated host response to infection that leads to life- threatening organ dysfunction, and is declared a global health priority by the World Health Organization. The objectives of this research were to compare the clinical and sociodemographic conditions of patients admitted to the Emergency Room, according to sepsis diagnosis and application of the sepsis protocol, and to verify the impact on outcomes associated with this application of the protocol, as well as to compare the impact of application of the sepsis protocol in the outcome of patients according to the comorbidities associated with sepsis, identify the outcome of the cases studied, in relation to the intervention measures of the sepsis package adopted, knowing the length of stay in days of patients with sepsis according to the application of the sepsis protocol, comparing the results of sepsis diagnoses according to the SOFA and ILAS consensuses and verifying whether different clinical scenarios , has different outcomes in the application of the sepsis protocol. This is an epidemiological, descriptive and analytical study, of the hospital-based mixed cohort type, carried out in the municipality of Ponta Grossa, Brazil, between November 2019 and October 2020. The analyzes were carried out in the R 4.0.4 environment. Of the 184 patients who had laboratory tests collected for the diagnosis of sepsis, 97 (52.72%) were male, 111 (60.33%) were elderly, 134 (72.83%) had clinical and laboratory criteria for sepsis, 59 (44.03%) received the sepsis protocol. A total of 118 (88.06%) patients with infection of community origin were admitted. Regarding the infectious topography, 78 (58.21%) were admitted with a respiratory infection. 38 (28.36%) patients died. The application of the sepsis protocol did not impact the length of hospital stay or mortality from sepsis. However, it was possible to deepen the knowledge about the profile of the septic patient and the needs for improvements.
Keywords: Sepse; Protocolos Clínicos; Serviço Hospitalar de Emergência; Mortalidade; Avaliação de Resultados em Cuidados de Saúde; Sepsis; Clinical Protocols; Hospital Emergency Service; Mortality; Evaluation of the results in Health Care; CNPQ::CIENCIAS DA SAUDE